Revealing the Neglected Missions: Some Comments on the Javanese Elements of Muhammadiyah Reformism - Burhani, Ahmad Najib (Studia Islamika, 2005)
This paper seeks to discuss Muhammadiyah's attitude towards the Javanese cultural identity in the movement interacted with the ideology, psychology, and cosmology of Javanese culture.The views, insights, and behaviour of the founding father and early prominent figures within the organisation are presented, notably the way in which the former interpreted elements of Javanese culture. To analyse the data available, this work attempts to explore and articulate the 'grammar of symbol'.DOI: 10.15408/sdi.v12i1.647